(untitled) (Research, Society and Development, 2022)
Brucellosis is one of the most important zoonoses in the world. It is an infectious disease caused by bacteria of the genus Brucella spp. which mainly affects the animal’s reproductive system, causing a drop in reproductive rates and an increase in the rate of abortion, thus causing economic losses in the livestock sector. In this sense, this work aimed to detect the presence of anti-Brucella sp. in buffaloes in the municipalities of Rolim de Moura and Santa Luzia D’Oeste, both in the state of Rondônia. As brucellosis is more important in female herds, blood samples were collected from 34 buffaloes, suitable for meat and milk, all of the Murrah breed, aged over 24 months, and examined with the buffered acidified antigen test (AAT) . Of the 34 samples, one was reactive to the test, suggesting that the animal was reactive to Brucella abortus. To confirm the data found, it is ideal that another diagnostic test confirming the disease is performed. A characteristic found only in the property of the reagent animal is the presence of wild animals at the site, which is a possible source of infection to the animals, and even though the prevalence of the study is considered low, it is important to emphasize that brucellosis is a disease zoonotic, it is important to discard positive animals in herds, in order to minimize possible infections both to other animals and humans.